2012
DOI: 10.1177/0306624x11434005
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ Obligation to Obey the Law

Abstract: For thousands of years, China primarily used morality for its social control. Since its economic reform starting in 1978, China has moved toward legal control. Two fundamental questions, however, remain understudied in China: (a) the degree to which citizens feel obligated to obey the law and (b) the sources of citizens' perceived obligation to obey the law. This study was intended to answer these questions based on random surveys of 1,196 residents from Guangzhou, China. The study revealed that the vast major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A recent study found that not all Australians complied fully with the lockdown restrictions, and compliance decreased slightly over time (Murphy et al, 2020). Although there is no research assessing Chinese willingness to obey the police, laws, or regulations during the pandemic, a pre-pandemic study shows the majority of Chinese citizens surveyed felt obligated to obey the law irrespective of their personal feelings (Jiang et al, 2013). It is reasonable to expect increased citizen compliance to reduce police stress.…”
Section: Police Stress During the Covid-19 Pandemicmentioning
confidence: 99%
“…A recent study found that not all Australians complied fully with the lockdown restrictions, and compliance decreased slightly over time (Murphy et al, 2020). Although there is no research assessing Chinese willingness to obey the police, laws, or regulations during the pandemic, a pre-pandemic study shows the majority of Chinese citizens surveyed felt obligated to obey the law irrespective of their personal feelings (Jiang et al, 2013). It is reasonable to expect increased citizen compliance to reduce police stress.…”
Section: Police Stress During the Covid-19 Pandemicmentioning
confidence: 99%
“…However, when establishing a stable social order, the citizens should abide by the law of their country. [1]…”
Section: Introductionmentioning
confidence: 99%